The informational content of subjective expectations for health service use - Nathan Kettlewell (BMC, 2021)
Abstract Background This study aims to evaluate the informational content of people's subjective probability expectations for using various health services. Methods Using a sample of 1,528 Australian adults (25-64 years), I compared stated probabilities of visiting various health service providers (hospitals, dentists, optometrists, physiotherapists and related care providers, naturopaths and massage therapists) with past utilization and with predicted utilization estimated out-of-sample. I also estimated whether past utilization and subjective expectations were predicted by the same covariates. Finally, I estimated whether subjective expectations had predictive power for the choice to purchase private health insurance conditional on past utilization and other controls. Results Subjective expectations closely reflect patterns of observed utilization, are predicted by the same covariates as observed utilization, and correlate with objective measures of risk. Subjective expectations also add predictive power to models estimating insurance take-up, even after conditioning on prior health care use and other risk factors. Conclusion The findings are indicative that on average people form quite accurate expectations, and support collecting subjective expectations about health services in household surveys for use in applied research.